FORMULASI DAN EVALUASI UJI MUTU FISIK LOTION EKSTRAK KULIT MANGGIS (Garcinia mangostana L.) - Fahmi Ardianti Purnawiranita; Vanny Ade Rahmasari (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
Mangosteen peel (Garcinia mangostana L.) contain xanton which used as antioxydant is good for the skin. The purpose of this study was to make lotion preparations which will be tested for the physical quality of the preparations. Extract of mangosteen peel made by maseration used ethanol 70% as solvent with rendemen value is 23,36%. The concentration used is 3%, 5%, and 7%. This study also evaluated the physical quality of the preparation which include organoleptic, pH test, homogeneity test, dispersive area, sticky test, identification of type emulsion. The results showed that the physical quality lotion distinctive flavor, light brown to dark brown, fine texture in formulations 3% and 5% whereas in the 7% formulation there are extract granules, Ph 6-6,5, dispersive area 3-7 cm, sticky test formulation 3% 3 minutes formulation 5% and 7% 5 minutes, and type of emulsion is oil in water